Before dawn [videorecording (DVD)] - Russell, Jarrad; Miller, Levi, 2002-; Jeffery, Travis, 1989-; Pollard, Myles; Franklin, Tim; Dulieu, Jordan; Sullivan, Peter, 1964-; Oxenbould, Ed, 2001-; Peacocke, Stephen, 1981- (Prince-Wright Productions, 2024)
Jim Collins, a young man from the outback, leaves his family-run sheep station to join the ANZAC and fight on the western front with hopes of making a difference. Soon, the realities of the muddy, ruthless, and entirely unforgiving war takes its toll on Jim. As the men in the battalion are whittled away and hope becomes a distant memory, a final chance at redemption at the Battle of the Hindenburg Line, one of Australia's greatest WW1 military victories. Jim must risk death or forever carry the burden of leaving yet another man behind. Based on real life war diaries, Before Dawn is an epic retelling of one of Australia's biggest victories during WW1.